Anorexia Nervosa (Homoeopathy for All, 2024)
Anorexia nervosa is a severe and potentially life-threatening psychiatric disorder characterized by a relentless pursuit of thinness, fear of gaining weight, and distorted body image. It affects individuals across various ages, genders, and socioeconomic backgrounds, with a higher prevalence among adolescents and young adults, particularly females. The disorder poses significant challenges to both individuals and healthcare providers due to its complex interplay of biological, psychological, and sociocultural factors.
Keywords: ANOREXIA NERVOSA; India; prevalence